Dissemination of Huller Technology to Increase Productivity in Gunung Kelir Robusta Coffee Industry - Sutrisno Sutrisno (Sekolah Vokasi Universitas Diponegoro, 2022)
Program for regional superior product (PPUD-DIKTI) year 2021 aims to increase income of coffee farmers who incorporated in Rahayu IV Gunung Kelir by introduction of huller. This introduction was done by considering that the farmers was potentially developed from coffee bean to coffee powder producers. PPUD was conducted by Teams from LPPM UNDIP. The program was excecuted in steps: i) designing of huller machine, ii) huller machine fabrication, iii) implementation, and iv) evaluation. Evaluation was performed by analyzing of increasing income for farmers at Rahayu IV. The huller ulper that utilized for coffee bean peeling was developed. The innovation was in its mobile characteristic so that the huller could be mobilized to cultivation place. The huller was designed dan fabricated with capacity of 1.000 kg/hour. Present of the huller could increase income of KUB Rahayu IV of Rp. 625.000 per day.